2013
DOI: 10.1126/scisignal.2003266
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Approach for Decoding Mitochondrial Retrograde Signaling Pathways

Abstract: Mitochondrial dysfunctions activate retrograde signaling from mitochondria to the nucleus. To identify transcription factors and their associated pathways that underlie mitochondrial retrograde signaling, we performed gene expression profiling of the cells engineered to have varying amounts of mitochondrial DNA with an A3243G mutation (mt3243) in the leucine transfer RNA (tRNA(Leu)), which reduces the abundance of proteins involved in oxidative phosphorylation that are encoded by the mitochondrial genome. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 72 publications
3
150
0
1
Order By: Relevance
“…45). In mammalian cells with an A3242G mutation of mitochondrial DNA, mitochondrial dysfuction altered expressions of several transcription factors including RXRA, which led to the decrease in PGC-1a recruitment and the repression of oxidative phosphorylation genes 46 . The involvement of PGC-1b in the retrograde signalling has not been reported, however, Pgc-1b may also have a role in the pathological condition of Cox7rpKO mice similar to Pgc-1a.…”
Section: Discussionmentioning
confidence: 99%
“…45). In mammalian cells with an A3242G mutation of mitochondrial DNA, mitochondrial dysfuction altered expressions of several transcription factors including RXRA, which led to the decrease in PGC-1a recruitment and the repression of oxidative phosphorylation genes 46 . The involvement of PGC-1b in the retrograde signalling has not been reported, however, Pgc-1b may also have a role in the pathological condition of Cox7rpKO mice similar to Pgc-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous work has shown that hybrid mitochondria in T. californicus have reduced ATP synthetic capacity [21], energy for preventive antioxidant activity and energy to repair damage is possibly reduced in hybrids. In addition to causing damage to cellular components, increased ROS levels activate numerous retrograde signalling pathways from mitochondria to the nucleus, which alter expression of many genes in both genomes and can affect important metabolic processes [48,49]. Moreover, dysfunctional ROS metabolism may undergo a positive feedback loop: increased oxidative damage can increase mitochondrial dysfunction, promoting further ROS accumulation [25,29].…”
Section: (C) Possible Sources and Consequences Of Oxidative Stress Inmentioning
confidence: 99%
“…In Drosophila, disruption of respiratory complex 1 signals to components of the G1 to S cell cycle machinery trough JNK and FoxO (Owusu-Ansah et al 2008). In mammalian cells, a similar retrograde signaling has been uncovered through a systematic analysis of different mitochondrial dysfunction mutations; this pathway increases OXPHOS genes and involves ROS signaling through JNK and the RXRa/ PGC1a pathway (Chae et al 2013). …”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%